Inpatient satisfaction level survey at a tertiary care hospital - Shekhawat, Shivani; Garg, Swati; Jain, Drishti; Sharma, Urvashi (International Journal of Research in Medical Sciences, 2016)
Background: Patient satisfaction is an important measure of quality of services in a healthcare organization. Other than the medical care issues, the satisfaction and experience involves personal relationships, attention to pain and health education, and the status of hospital environment. Patient’s opinion is an important because dissatisfaction suggests opportunities for improvement of health services in the hospital. This study was done with the aim to assess the satisfaction levels in inpatients of a tertiary care hospital and to compare interdepartmental satisfaction scores in the same hospital. Methods: This cross-sectional survey was done in inpatients of the department of general medicine, general surgery and obstetrics & gynaecology wards of Mahatma Gandhi Medical College & Hospital, Jaipur for two consecutive days. A total of 150 adult female patients were included in the study. Structured questionnaire was developed from previously used survey tools, and validated in present patients group, and patient satisfaction was checked. Results: The demographic data of patients showed that majority of respondents were belonged to age group 20-30 years (50.7%) followed by less than 20 years (20%), more than 40 years (15.3%) and 30-40 years (12%). About 29.33% respondents were uneducated followed by primary level (25.33%), senior secondary level (24%) and graduation (21.33%). 90% respondents belonged to Hindu religion. 36.6% of the respondents were either technicians or doing a clerical job. Almost equal numbers (33.3%) were unemployed and 30% belonged to the labour class. Only 15 patients (10%) were either professionals or on managerial posts. Conclusions: This study highlighted overall patient satisfaction was good regarding the quality of health care services of Mahatma Gandhi Medical College and Hospital. Areas where patient satisfaction was found to be lowest were patience shown by the nursing staff while communicating with patients and hospital ambiance in terms of peacefulness, both of these are important aspects of health care and there is imperative need to address these problems effectively and urgently in order to improve quality of care.